2012
DOI: 10.1155/2012/205393
|View full text |Cite
|
Sign up to set email alerts
|

Weight Misperceptions and Racial and Ethnic Disparities in Adolescent Female Body Mass Index

Abstract: This paper investigated weight misperceptions as determinants of racial/ethnic disparities in body mass index (BMI) among adolescent females using data from the National Survey of Youth 1997. Compared to their white counterparts, higher proportions of black and Hispanic adolescent females underperceived their weight status; that is, they misperceived themselves to have lower weight status compared to their clinically defined weight status. Compared to their black counterparts, higher proportions of white and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
1
16
2
Order By: Relevance
“…Specifically, using self-reported weight and height data as compared with actual weight and height data may result in lower occurrences of underestimation and higher occurrences of overestimation. Consistent with studies that examined weight misperception among adolescents, 6,12,13,16,24 we found that male subjects were more likely than female subjects to misperceive their weight status using either methodology. In addition, female subjects were more likely than male subjects to overestimate, whereas male subjects were more likely to underestimate their weight status, findings that are consistent with previous research.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, using self-reported weight and height data as compared with actual weight and height data may result in lower occurrences of underestimation and higher occurrences of overestimation. Consistent with studies that examined weight misperception among adolescents, 6,12,13,16,24 we found that male subjects were more likely than female subjects to misperceive their weight status using either methodology. In addition, female subjects were more likely than male subjects to overestimate, whereas male subjects were more likely to underestimate their weight status, findings that are consistent with previous research.…”
Section: Discussionsupporting
confidence: 88%
“…[34][35][36] African and Hispanic American girls have been found to underestimate their own weight status, whereas white girls overestimate their weight. 37 This phenomenon may have been a factor when white females in this sample selected or nominated their friends. It is possible that white girls may have not selected (or nominated) friends of weight statuses different then themselves because of their own weight misperceptions or concerns: White overweight girls may be concerned about being overweight, and therefore weight status may matter more in choosing friends.…”
Section: Discussionmentioning
confidence: 95%
“…35 Flawed weight classification in childhood can set in motion lifelong distorted perceptions of what is acceptable, contributing to adolescent and adult obesity. 36,37 Rising rates of youth obesity theoretically account for a reduction of between two and five years in average lifespan, 38,39 and are expected to shorten overall life expectancy in the U.S. for the first time in two centuries. 38 Timely diagnosis of abnormal weight status for children is critical, and prevention efforts are challenging, given that many parents of obese children are unlikely to initiate action to prevent obesity 1) if weight is not perceived as a problem, or 2) if the link between current and future adverse health outcomes is not appreciated.…”
Section: Discussionmentioning
confidence: 99%